Clinical evaluation of functional vision of +1.5 diopters near addition, aspheric,rotational asymmetric multifocal intraocular lens - Kretz, Florian Tobias Alwin; Khoramnia, Ramin; Attia, Mary; Koss, Michael Janusz; Linz, Katharina; Auffarth, Gerd U. (Korean journal of ophthalmology, 2016)
Kretz FT, et al. Korean J Ophthalmol. 2016 Oct;30(5):382-389. https://doi.org/10.3341/kjo.2016.30.5.382
Gesehen am 27.05.2020